Impact of early eyelid weight placement on the development of synkinesis and recovery in patients with idiopathic facial paralysis - Keon M. Parsa (KeAi Communications Co., Ltd., 2021)
Purpose: Determine the impact of upper eyelid weight placement at 3 months post onset of idiopathic facial paralysis (IFP) on the recovery of facial function in patients with lagophthalmos. Methods: This is a retrospective review of patients with incomplete recovery of IFP—defined as a Sunnybrook Facial Grading Scale (FGS) score of less than 100, 3 months after onset. Only patients with FGS and Facial Clinimetric Evaluation (FaCE) scores recorded at 3 and 12 months were included. Patients were categorized into 3 groups: Group A, lagophthalmos with eyelid weight placement; Group B, lagophthalmos without eyelid weight placement; Group C, complete eye closure (CEC) without eyelid weight placement. The eye comfort domain and composite score of the FaCE questionnaire were analyzed. Voluntary eye closure, synkinesis with eye closure, overall synkinesis and the composite score of the FGS were also analyzed. Paired two-tailed t-test was used to evaluate the data comparing the 3 and 12 month FaCE and FGS scores within and between the 3 groups. Results: The change in composite FGS score significantly increased from month 3 to month 12 in Group A as compared to Group B (37 vs 4.25, P = 0.01). While Group A had significantly lower eye comfort (−12.5, P = 0.01), voluntary eye closure (−1.75, P = 0.05) and overall FGS scores (−28.75, P = 0.04) at 3 months compared to those in Group C, there were no differences between these two groups at 12 month follow-up. Conclusions: For patients with lagophthalmos at 3 months, early eyelid weight placement may lead to improved facial function at 12 months.